Visual sustained attention and executive functions in children with developmental dislexia - Franco de Lima, Ricardo; Pinheiro Travaini, Paula; Alves Salgado Azoni, Cintia; Maria Ciasca, Sylvia (Anales de Psicología / Annals of Psychology, 2012)
Introdution: Alterations in attention and executive functions have been described in dyslexia despite the conflicting results.Objective: To compare the performance of children with dyslexia and without difficulties in tests of attention and executive functions. Methods: Participated 50 students divided into: 25 with dyslexia and 25 without learning difficulties. The instruments were used: Trail Making Test, Tests of Cancellation, Stroop Color Word Test and Tower of Lon- don. The scores of the tests were compared between groups. Results: The group with dyslexia showed poorer performance with the tests, except the Tower of London. Conclusion: The results suggest that dyslexics may show changes in visual sustained attention and some aspects of executive functions: flexibility and cognitive inhibition, but not in planning. Changes in components execu- tives can monitor the core deficit in phonological processing in dyslexia.